Absorption of Nickel, Chromium, and Iron by the Root Surface of Primary Molars Covered with Stainless Steel Crowns - David Keinan; Eliyahu Mass; Uri Zilberman (International Journal of Dentistry)
Objective. The purpose of this study was to analyze the absorption of metal ions released from stainless steel crowns by root surface of primary molars. Study Design. Laboratory research: The study included 34 primary molars, exfoliated or extracted during routine dental treatment. 17 molars were covered with stainless-steel crowns for more than two years and compared to 17 intact primary molars. Chemical content of the mesial or distal root surface, 1 mm apically to the crown or the cemento-enamel junction (CEJ), was analyzed. An energy dispersive X-ray spectrometer (EDS) was used for chemical analysis. Results. Higher amounts of nickel, chromium, and iron (5-6 times) were found in the cementum of molars covered with stainless-steel crowns compared to intact molars. The differences between groups were highly significant (𝑃<.001). Significance. Stainless-steel crowns release nickel, chromium, and iron in oral environment, and the ions are absorbed by the primary molars roots. The additional burden of allergenic metals should be reduced if possible.